Pengkalan data teragih dalam persekitaran IBM PC LAN 1.3 : eksperimen - Abdullah, Abdul Hanan (Penerbit UTM Press, 1990)
This paper explains the experiment that uses the IBM PC LAN 1.3 package that offer services to Local Area Network under the token ring environment. The purpose is to check the capabilities of the package to provide a distributed database system for the general practice clinics. For the implementation, DBASE III PLUS is used to develop the information system. The experiment is carried out using the facilities at the Institute of Computer Science. The prototype system developed from the experiment is discussed in details. Proposal to improve the system is also discussed.